235k views
1 vote
Rewrite the function by completing the square.

g(x) = 2x^2 – 7x + 5
g(x) =...(x+...)^2+...

User Ergys
by
5.0k points

2 Answers

4 votes

Answer:

g(x) = 2(x - 1.75)^2 - 1.125.

Explanation:

g(x) = 2x^2 – 7x + 5

First take the 2 out of the first terms:

g(x) = 2(x^2 - 3.5x) + 5

Now complete the square on the expression in the parentheses:

g(x) = 2 [ (x - 1.75)^2 - 1.75^2] + 5

g(x) = 2 [ (x - 1.75)^2 - 3.0625] + 5

g(x) = 2(x - 1.75)^2 - 6.125 + 5

g(x) = 2(x - 1.75)^2 - 1.125.

User Crymson
by
4.8k points
2 votes

Answer:

2(x -
(7)/(4) )² -
(9)/(8)

Explanation:

Given

2x² - 7x + 5

The coefficient of the x² term must be 1, thus factor out 2 from 2x² - 7x

= 2(x² -
(7)/(2) x ) + 5

To complete the square

add/ subtract ( half the coefficient of the x- term )² to x² -
(7)/(2) x

= 2(x² + 2(-
(7)/(4) )x +
(49)/(16) -
(49)/(16) ) + 5

= 2(x -
(7)/(4) )² -
(98)/(16) + 5

= 2(x -
(7)/(4) )² -
(18)/(16)

= 2(x -
(7)/(4) )² -
(9)/(8)

User Hexonxons
by
5.4k points